Clio and the economist: Making historians count - Greasley, D.; Oxley, Leslie (Wiley-Blackwell, 2010)
Cliometrics reconnected economic history and economics in the 1960s. The deeper foundations of cliometrics research lie in the longer standing traditions of quantitative history and the contemporaneous growth of the social sciences and computing. Early cliometrics research reinterpreted economic history through the lens of neo-classical economics. Over the past half century cliometrics has matured and now utilizes a broad array of theoretical perspectives and statistical methods to help understand the past. The papers introduced here illustrate the achievements of several key areas of cliometrics research and show how new theoretical perspectives, innovative data construction and sophisticated econometric methods are the hallmarks of the discipline. © 2010 Blackwell Publishing Ltd.